PRICE TRANSMISSION ANALYSIS ALONG THE FOOD CHAIN - Gani Kalikulovich, Turabayev (British Journal of Marketing Studies, 2014)
Vertical price transmission between wheat and flour markets in Kazakhstan has been analyzed using monthly data during the period 2000-2010. Officials applied a wide variety of policies in response to global wheat price increases, often causing adverse and unintended effects on regional domestic wheat and flour prices. Overall, short-run policies aimed especially at mitigating wheat and flour prices were unsuccessful, causing greater instability and uncertainty in domestic market. The results confirm that price transmission between wheat and flour switched over the period. The PMG model was performed separately with the two regimes, and indicated that price transmission significantly altered under regime changes. Although overall coefficient differences in the two regimes are modest, the results across regions have different patterns in depicting huge differences in coefficients and magnitude. Moreover, The Granger causality test implies that the global wheat price is a good determinant of price differences across oblasts (regions)